Probiotic and Postbiotic Potentials of Enterococcus faecalis EF-2001: A Safety Assessment - Kwon Il Han; Hyun-Dong Shin; Yura Lee; Sunhwa Baek; Eunjung Moon; Youn Bum Park; Junhui Cho; Jin-Ho Lee; Tack-Joong Kim; Ranjith Kumar Manoharan (MDPI AG, 2024)
Background: Probiotics, which are live microorganisms that, when given in sufficient quantities, promote the host's health, have drawn a lot of interest for their ability to enhance gut health. Enterococcus faecalis, a member of the human gut microbiota, has shown promise as a probiotic candidate due to its functional attributes. However, safety concerns associated with certain strains warrant comprehensive evaluation before therapeutic application. Materials and Methods: In this study, E. faecalis EF-2001, originally isolated from fecal samples of a healthy human infant, was subjected to a multi-faceted assessment for its safety and probiotic potential. In silico analysis, CAZyme, biosynthetic, and stress-responsive proteins were identified. Results: The genome lacked biogenic amine genes but contained some essential amino acid and vitamin synthetic genes, and carbohydrate-related enzymes essential for probiotic properties. The negligible difference of 0.03% between the 1st and 25th generations indicates that the genetic information of the E. faecalis EF-2001 genome remained stable. The live E. faecalis EF-2001 (E. faecalis EF-2001L) demonstrated low or no virulence potential, minimal D-Lactate production, and susceptibility to most antibiotics except some aminoglycosides. No bile salt deconjugation or biogenic amine production was observed in an in vitro assay. Hemolytic activity assessment showed a β-hemolytic pattern, indicating no red blood cell lysis. Furthermore, the EF-2001L did not produce gelatinase and tolerated simulated gastric and intestinal fluids in an in vitro study. Similarly, heat-killed E. faecalis EF-2001 (E. faecalis EF-2001HK) exhibits tolerance in both acid and base conditions in vitro. Further, no cytotoxicity of postbiotic EF-2001HK was observed in human colorectal adenocarcinoma HT-29 cells. Conclusions: These potential properties suggest that probiotic and postbiotic E. faecalis EF-2001 could be considered safe and retain metabolic activity suitable for human consumption.